Investigation of different methods of intraoperative graft perfusion assessment during kidney transplantation for the prediction of delayed graft function: a prospective pilot trial - Gerken, Andreas; Keese, Michael; Weiß, Christel; Krücken, Hanna-Sophie; Pecher, Katarina; Ministro, Augusto; Rahbari, Nuh Nabi; Reißfelder, Christoph; Rother, Ulrich; Yazdani, Babak; Kälsch, Anna-Isabelle; Krämer, Bernhard; et al. (Journal of Personalized Medicine, 2022)
Delayed graft function (DGF) after renal transplantation is a relevant clinical problem affecting long-term organ function. The early detection of patients at risk is crucial for postoperative monitoring and treatment algorithms. In this prospective cohort study, allograft perfusion was evaluated intraoperatively in 26 kidney recipients by visual and formal perfusion assessment, duplex sonography, and quantitative microperfusion assessment using O2C spectrometry and ICG fluorescence angiography. The O2C tissue spectrometry device provides a quantitative method of microperfusion assessment that can be employed during kidney transplantation as an easy-to-use and highly sensitive alternative to ICG fluorescence angiography. Intraoperative microvascular flow and velocity in the allograft cortex after reperfusion predicted DGF with a sensitivity of 100% and a specificity of 82%. Threshold values of 57 A.U. for microvascular flow and 13 A.U. for microvascular velocity were identified by an ROC analysis. This study, therefore, confirmed that impairment of microperfusion of the allograft cortex directly after reperfusion was a key indicator for the occurrence of DGF after kidney transplantation. Our results support the combined use of intraoperative duplex sonography, for macrovascular quality control, and quantitative microperfusion assessment, such as O2C spectrometry, for individual risk stratification to guide subsequent postoperative management.
Dieser Artikel gehört zum Special issue: Application of medical imaging in cancer screening, diagnosis, and personalized treatment
Gesehen am 07.08.2023